A case of pseudotumor cerebri and brucellosis - Emadoleslami, Monir; Mahmoudian, Touran (Journal of Pediatric Infectious Diseases, 2007)
We report a patient who presented with symptoms and signs of brucellosis and pseudotumor cerebri. Brucellosis is a common and endemic disease in Isfahan. Different patterns and manifestations, which are seen in this disease, may complicate the diagnosis. Pseudotumor cerebri has been reported in limited number of articles as an early sign for brucellosis. We report more details about the patient's signs, symptoms and serologic diagnosis of this condition in this article. We treated our patient with rifampin and doxycycline and gentamicin for 6 months. She had a complete recovery after 3 months.
Keywords: Pseudotumor cerebri; brucellosis